Intrusion Prevention System Inspired Immune Systems - Yousef Farhaoui (Institute of Advanced Engineering and Science, 2016)
In view of new communication and information technologies that appeared with the emergence of networks and Internet, the computer security became a major challenge, and works in this research axis are increasingly numerous. Various tools and mechanisms are developed in order to guarantee a safety level up to the requirements of modern life. Among them, intrusion detection and prevention systems (IDPS) intended to locate activities or abnormal behaviors suspect to be detrimental to the correct operation of the system. The purpose of this work is the design and the realization of an IDPS inspired from natural immune systems. The study of biological systems to get inspired from them for the resolution of computer science problems is an axis of the artificial intelligence field which gave rise to robust and effective methods by their natural function, the immune systems aroused the interest of researchers in the intrusion detection field, taking into account the similarities of NIS (Natural Immune System) and IDPS objectives. Within the framework of this work, we conceived an IDPS inspired from natural immune system and implemented by using a directed approach. A platform was developed and tests were carried out in order to assess our system performances.